THE INTERIOR MINISTRY AND THE AUDIT CHAMBER OF RUSSIA: PROSECUTION FOR FINANCIAL AND FISCAL OFFENSES - A. A. Morukova; S. V. Kalinina (Финансы: теория и практика, 2017)
Based on the analysis of regulatory legal acts governing the activities of the Russian Audit Chamber of the Russian Federation, as well as on the information from the official websites of the mentioned agency and the Ministry of Internal Affairs of the Russian Federation, the article considers the issues of cooperation between control and audit and law enforcement agencies in view to subject the offenders to administrative sanctions. The authors reveal the aspects related to the amount of damage and scope of administrative violations in the economic sphere, including the budgetary area. It is noted that currently such breaches cause significant material damage and account for about 7.5% of the budget expenditures. The authors stress that it is unacceptable in the situation of budget deficit and strict austerity. First, the main real problem in organization of cooperation and interaction between the control and audit and internal affairs agencies involved in prevention, suppression and detection of offenses is the lack of a regulatory legal act which would establish such an arrangement for cooperation. Second, there is a problem related to the fact that the employees of internal affairs bodies are not authorized for functions of revealing administrative violations in the economic sphere. The authors believe that a better use of the potential of interaction between the law enforcement bodies and the Audit Chamber of Russia may help solve the identified problems.